Evaluation of maxillary sinus after Le Fort I osteotomy using various fixation materials. Issue 4 (April 2017) - Ueki, Koichiro; Yoshizawa, Kunio; Moroi, Akinori; Hotta, Asami; Tsutsui, Takamitsu; Fukaya, Kenichi; Hiraide, Ryota; Takayama, Akihiro; Tsunoda, Tatsuya; Saito, Yuki; Iguchi, Ran; Kosaka, Akihiko; et al.
Abstract: Purpose: The purpose of this study was to evaluate maxillary sinus and predict the factors affecting the postoperative sinus condition after Le Fort I osteotomy using various fixation materials. Materials and methods: The study subjects consisted of 71 patients (21 male and 50 female, 142 sides) who underwent Le Fort I osteotomy with sagittal split ramus osteotomy. The maxillary sinus bony area and the inside air area were measured in the coronal plane across the mesial aspect of the first molar perpendicular to the Frankfurt horizontal plane of a computed tomography (CT) image preoperatively and at 1 week and 1 year after surgery. The rate of intact sinus area (the inside air area/the maxillary sinus bony area) was calculated. Subjects were divided into groups according to gender, preoperative diagnosis (Angle class II and III with and without asymmetry), plate fixation material (PLLA and uHA/PLLA), and use or non-use of bone alternative material (α-tricalcium phosphate). Statistic comparisons between groups were performed in each division. Furthermore, age, operation time, amount of blood loss, and direction and amount of movement were examined as the continuous variables to statistically predict the rate of intact sinus area after 1 week and 1 year. Results: The rate of intact sinus area after 1 week was significantly correlated with age, amount of anterio-posterior movement, and preoperative rate of the intact sinus area (p < 0.0001). Rate of intact sinus area after 1 year was significantly low in the group that used the bone alternative material compared to the group that did not (p < 0.0282). Conclusion: The study suggests that the bone alternative material might be a cause of inflammation in the sinus after 1 year. Moreover, attention needs to be paid to older age, backward movement of the maxillary segment, and preoperative sinusitis including hypertrophy of sinus membrane in Le Fort I osteotomy.